Meta-analysis of the efficacy and safety of prazosin versus placebo for the treatment of nightmares and sleep disturbances in adults with posttraumatic stress disorder. Issue 4 (7th August 2016) - George, Kirsten C.; Kebejian, Lisa; Ruth, Leigh J.; Miller, Christopher W. T.; Himelhoch, Seth
ABSTRACT: Although sleep disturbances occur commonly in patients with posttraumatic stress disorder (PTSD) and are associated with adverse outcomes and increased suicidality, they are often inadequately addressed by antidepressant medications. Objective : This review aims to assess whether prazosin reduces nightmares, sleep disturbances, and illness severity in adults with PTSD. Method : Electronic databases (PubMed, PsycINFO) were searched in September 2014 for randomized controlled trials in adults. Search terms included posttraumatic stress disorder, prazosin, nightmares, and sleep disturbance . Included studies used prazosin and provided objective outcome data related to nightmares and/or sleep quality. Results : Six studies (191 participants) met the criteria for inclusion. Prazosin was more effective than placebo in improving nightmares (standardized mean difference [SMD] = 1.022, 95% confidence interval [CI] [0.41, 1.62], p  = .001), sleep quality (SMD = 0.93, 95% CI [−0.02, 1.88], p  = .054; and SMD = 1.14, 95% CI [0.24, 2.03], p  = .01), and illness severity (SMD = 1.20, 95% CI [0.79, 1.61], p = .001, with no significant effect on systolic (SMD = −0.01, 95% CI [−0.40, 0.37], p  = .94) or diastolic (SMD = 0.30, 95% CI [−0.09, 0.68], p  = .154) blood pressure. Conclusion : PTSD-related nightmares, sleep disturbances, and overall illness severity showed a significant response to treatment with prazosin. With careful dose titration, prazosin was well tolerated and had no significant sustained effect on blood pressure.